Quality of Parental Nurturing and its Influence on Adolescents' Aggressive Behavior in Selected Public Secondary Schools in the North West and Center Regions of Cameroon - Carene, Youmbi Mbenowol; Nsagha Sarah Mboshi; Lum Bobga Jacqueline Achiri (Researchparks Publishing, 2025)
It has been realized that majority of adolescents students in Cameroonian public secondary schools are manifesting antisocial behaviors in different forms as opposed to expected behavior. The purpose of the study was to examine the influence of psychosocial determinants on adolescents’ aggressive behaviour in selected public secondary schools in Cameroon. The four specific objective of the study were, to assess the influence of shift in parental role on aggressive behaviour in adolescents; to find out the quality of parental nurturing on adolescents that influences aggressive behaviour; to find out the influence of peer influence on adolescents; and to examine the influence of conformity to peer culture aggressive behaviour. These objectives were transformed into hypotheses. Theoretically, the study was guided by Erikson theory of psychosocial development, Bandura theory of social learning, and Maslow’s theory of needs. Methodologically, the concurrent mixed method research design was used in conducting this study and data were collected from 435 form three and four students, using a questionnaire and 100 parents using a structured interview guide. Probability and non-probability sampling techniques were used to sample the respondents. The validity and reliability of the questionnaire stood at 0.97 and 0.837 respectively while that of the interview guide was rated using the need analysis approach. Quantitative data collected were analysed using descriptive and inferential statistics with the support of SPSS 25.0 while qualitative data were analysed thematically. The quantitative statistical techniques used were percentages, mean, standard deviation, and linear regression. The findings showed that a significant proportion of students 58.0% display several aggressive behaviours toward others. More so, 60.8% of students were influence by peers in many ways, 68.0% conform to pressure from others in many aspects, 35.8% were experiencing shift in parental role in many of their activities, and 30.3% do not enjoy quality parental nurturing especially those from working class parents. And it was finally, revealed that for every unit of shift in parental role, adolescents’ aggressive behaviours is more likely to increase by 0.310, significant at 1% level (Coefficient value =0.310, p-value < 0.05). More so, for every unit of improvement in quality in parental nurturing, adolescents’ aggressive behaviours is more likely to decrease by 0.496, significant at 1% level. (Coefficient value = -0.496, p-value < 0.05). Again, findings showed that for every unit of peer influence, adolescents’ aggressive behaviours is more likely to increase by 0.420, significant at 1% level. (Coefficient value =0.420, p-value < 0.05). Finally, for every unit of conformity pressure, adolescents’ aggressive behaviours is more likely to increase by 0.441, significant at 1% level (Coefficient value =0.441, p-value < 0.05). Based on these findings, it was recommended that parents should ensure a balance work family life, spend quality time with children, and schools should restructure their disciplinary infrastructure for better prevention and management of school violence.